Strengthening Religious Provisions in the Era of Social Media for Children in the Ex-Localization Panjang Lampung - Yanti, Fitri; Amaliah, Eni (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This article aims to illustrate and explain the social media era religious guidance activities for children in the ex-localization of Bandar Lampung. The author uses a qualitative sampling design or the determination of informants is done directly (purposive).This article reveals that religious guidance is needed in shaping and fostering religious life through social media because the intensity of interaction is more dynamic and all parties can be subject to information with a network that is open to everyone. The current level of influence of social media on religious life is important to know. The result is the strengthening of religious and religious services making two policy implications, namely the development of integrative insights between formal and non-formal education and strengthening the insight of the use of devices, smartphones so that the function of religious messages delivered is running optimally